Transcatheter edge‐to‐edge tricuspid repair for recurrence of valvular regurgitation after left ventricular assist device and tricuspid ring implantation - Martin Andreas; Marco Russo; Paul Werner; Matthias Schneider; Franziska Wittmann; Sabine Scherzer; Julia Mascherbauer; Alfred Kocher; Guenther Laufer; Dominik Wiedemann; Daniel Zimpfer (ESC Heart Failure)
Abstract Tricuspid regurgitation in patients with left ventricular assist device (LVAD) has a significant impact on prognosis and quality of life, and its effects on liver and renal function could negatively impact planned heart transplantation. The aim of the present case is to report the feasibility and the clinical impact of tricuspid transcatheter edge‐to‐edge repair in LVAD patients as adjunctive bridge to transplantation strategy. A 59‐year‐old female patient previously treated with LVAD implantation (HeartMate III) and tricuspid valve repair with 32 mm rigid ring (Medtronic Contour 3D) as bridge to transplantation developed recurrence of significant tricuspid regurgitation with right ventricular decompensation needing inotropic support. Preoperative echo showed torrential tricuspid valve regurgitation Effective regurgitant orifice area(EROA 1.4 cm2) with suspicious of partial detachment of the prosthetic ring. The patient was successfully treated with transcatheter edge‐to‐edge repair with the MitraClip XTR device. Tricuspid regurgitation was reduced by 50% (postoperative EROA 0.7 cm2). She remained stable under continuous inotropic support with no other episodes of right ventricular decompensation and was successfully transplanted 30 days after the clipping procedure. Transcatheter treatment of tricuspid regurgitation in a patient with LVAD was an effective strategy to gain time and bridge the patient to heart transplantation.